Analisis Konsep Investasi Menurut Ekonomi Syariah : Tinjauan Hukum, Etika dan Prinsip Syariah - Faza, Shabrina Dwi Nouva Nur (Maliki Interdisciplinary Journal, 2025)
Investment plays a crucial role in driving economic growth through job creation, increased productivity, and market expansion. In Islamic economic law, investment not only aims to achieve financial profit but also supports principles of justice, sustainability, and public welfare. Islamic investment avoids practices prohibited by Shariah, such as riba, gharar, and maysir, utilizing instruments like mudharabah, musyarakah, and sukuk to ensure fair distribution of risks and returns. Shariah-compliant capital markets, Islamic stocks, sukuk, and Shariah mutual funds are key instruments in Islamic investment, all overseen by the Shariah Supervisory Board. Despite its significant potential, the implementation of Islamic investment faces challenges, such as a lack of Shariah financial literacy, limited investment instruments, and suboptimal regulations. To address these challenges, there is a need for education, product innovation, regulatory enhancement, human resource development, and international collaboration. Islamic investment, grounded in strong Shariah principles, not only generates economic profit but also provides social and spiritual benefits to society.